DAYA ANTIBAKTERI EKSTRAK ETANOL DAUN SENGGANI (Melastoma affine D. Don) - Ika Trisharyanti Dian Kusumowati; Rosita Melannisa; Angga Prasetyawan (Universitas Muhamadiyah Surakarta, 2014)
Melastoma affine D. Don had some activities such as anthelmintic, antibacteria, antiinfiammation, antifungal, and antitumor. The aims of this research was determine antibacteria activity of ethanolic extract of Melastoma affine D. Don. The antimicrobial activity was tested by solid dilution method to get Minimum Inhibition Concentration (MIC). The compounds in Melastoma affine D. Don was analyzed by tube test method and Thin Layer Chromatography (TLC) with chloroform : methanol : formic acid (8,5:1,5:0,5) as mobile phase and silica gel GF254 as stationary phase. The result showed ethanolic extract of Melastoma affine D. Don contains alkaloid, polyphenol, fiavonoid, saponin, and essential oil. The MIC of Senggani against Staphylococcus aureus was 2% and 3% against Escherichia coli and the extract could not inhibit Staphylococcus aureus and Escherichia coli multiresistant until concentration 7% extract ethanol.Keywords: Melastoma affine D. Don, Staphylococcus aureus, Escherichia coli